The Effect of Corruption on Economic Development in Nigeria (Global Journal of Human-Social Science, 2022)
The study examines the effects of corruption on economic development and growth in Nigeria Corruption is conduct that deviates from the normal duties of public trust due mainly to the expectation of private pecuniary reward The study purposes that corruption is the bane of economic development and growth in Nigeria The study adopted the historical descriptive method and sourced materials primarily from secondary sources The study also adopted the prebendal theoretical framework Findings from the study show that corruption retards economic development and growth promotes bad governance poor service delivery uncoordinated policies and programmes decayed infrastructures impunity by officials of government brain drain moral decadence and encourages leadership ineptitude The study therefore recommends massive attitudinal re-orientation and public enlightenment compulsory declaration of assets and liabilities of government officials before and after office plugging of leakages greater operational autonomy to anti-corruption agencies the establishment of a special court to handle corruption cases and the development of the strong institution and people-oriented and visionary leadership as the panacea for tackling corruption frontally in the country